Impact of environmental factors on the antibacterial activity of leaf extracts from Moroccan strawberry trees (Arbutus unedo L.) - Oussif, Ilias; Salim, Nora; El Habty, Mohamed; Wahid, Nadya (Australian Journal of Crop Science, 2025)
The present work determines the environmental factors and evaluates origin effect of leaf extracts from natural populations of the Moroccan strawberry tree (Arbutus unedo L.) on the potential antibacterial activity of human pathogenic strains. Samples of strawberry tree from different geographically distinct areas were collected for methanolic dried leaf extraction by tree/ population. Each leaf methanolic extract were analysed for antioxidant compounds and antibacterial activity test. The results show a variation in antibacterial activity depending on the concentration of the extract and on the origin of the plant material used for the preparation of the methanolic extracts. The bacterial strains tested were susceptible to the antibacterial effects of the methanolic leaf extract even at a lower concentration of 25 mg/ ml, indicating that the extract is potent enough to affect the bacteria at this lower dosage. The analysis of variance shows a significant provenance effect of Moroccan Arbutus extracts on the inhibition of the antibacterial activity zone of the strains at low and medium concentrations. The results of the geographical structure of Arbutus leaf extracts classified populations into three groups. The first group is composed of (OUL, IKA, DAR) populations which can synthesize phenolic active compounds against the Escherichia coli, Enterococcus faecalis, Klebsiella pneumoniae bacteria. The second group (ZRI, BT) is characterized by high precipitation and high antibacterial activity only against Citrobacter freundii. The third group (TIM, ELK, BS, OUM, BRI, IZA) is represented by the presents a negative correlation for all the antioxydante componends and antibacterial activity. This population structure of Arbutus leaf extracts results shows that the antioxidant compounds from populations of high altitude and more humid origins have weak antibacterial effects against the four tested strains. Leaf extracts from populations originating from low altitudes with moderate precipitation record high antibacterial effects. The determination of the effect of the environment on the phytochemical composition of Arbutus leaf extracts, and indirectly on the inhibition activity of the antibacterial zone, is necessary to select elite natural population products for applications in the food, therapeutic and pharmaceutical fields.